Mediate transgastric hepaticostomy: about its differences with the Gohrbandt and Dogliotti hepaticogastrostomies - Praderi, Raúl; Mazza, Milton; Gómez Fossati, Carlos; Estefan, Alberto; Davidenko, Nicolás (Cirugía del Uruguay, 1974)
The different techniques of biliogastric anastomosis: common hepaticogastrostomy, Hepaticocolecystogastostomy and Hepaticogastostomy of Gohrbandt and Dogliotti, have been analized. All of them are not standing nowadays. Seven observations of biliogastric anastomosis with various techniques are summarily reported. Among them three (transgastric hepatostomies) with transhepatic "U" tubes are poi nted out. All of the treated cases were advanced biliary cancer, with the exception of sclerosing colangitis. With a simple and quick operation, this procedure allows the drainage of the bile from the hepatic .to the stomach, leaving a changeable tube passed through between the liver and the stomach without need of suturing one organ with the other. It is used in patients in serious conditions with limited overliving, instead of doing left hepatico-jejunostomies, that are more laborious operations for this kind of patients.